Case Control Study: Individual and Comparative Assessment of Risk Factors as A Cause of Esophageal Cancer - Sapna Y Maheshram (Medsci Publications, 2016)
Introduction: The association between smokeless tobacco, betel nut and Esophageal Squamous Cell Carcinoma is not much researched area. Hence the assessment of individual risk factors as a cause of esophageal cancer was done in general population. Method: A case-control study was carried out over a period of 3 years among 690 (230 cases and 460 controls) subjects. All incident squamous cell carcinoma cases were recruited at The Tata Memorial Hospital. A structured pretested questionnaire was used to collect the data through face-to-face interview of the participants. Results: The ever use of pan, betel nut, tobacco chewing, masheri application, bidi, cigarette smoking and alcohol consumption were having significantly higher odds when the subjects who had never consumed these products were taken as referent. The frequency (amount consumed per day) and duration of use of all the above mentioned entities were also found to be significantly associated with ESCC (p<0.01) for all. Conclusion: All these proven risk factors are potentially preventable at the primary stage, hence health education regarding the hazards need to be incorporated in the school and college syllabus, along with strict implementation of Anti tobacco laws.